The combined effects of lanthanum-modified bentonite and Vallisneria spiralis on phosphorus, dissolved organic matter, and heavy metal(loid)s - Chen, Xiang; Liu, Ling; Wang, Yan; Zhou, Li; Xiao, Jing; Yan, Wenming; Li, Minjuan; Li, Qi; He, Xiangyu; Zhang, Lan; You, Xiaohui; Zhu, Dongdong; et al. (The Science of the total environment, 2024)
The use of lanthanum-modified bentonite (LMB) combined with Vallisneria spiralis (V∙s) (LMB + V∙s) is a common method for controlling internal phosphorus (P) release from sediments. However, the behaviors of iron (Fe) and manganese (Mn) under LMB + V∙s treatments, as well as the associated coupling effect on P, dissolved organic matter (DOM), and heavy metal(loid)s (HMs), require further investigations. Therefore, we used in this study a microelectrode system and high-resolution dialysis technology (HR-Peeper) to study the combined effects of LMB and V∙s on P, DOM, and HMs through a 66-day incubation experiment. The LMB + V∙s treatment increased the sediment DO concentration, promoting in-situ formations of Fe (III)/Mn (IV) oxyhydroxides, which, in turn, adsorbed P, soluble tungsten (W), DOM, and HMs. The increase in the concentrations of HCl-P, amorphous and poorly crystalline (oxyhydr) oxides-bound W, and oxidizable HMs forms demonstrated the capacity of the LMB + V∙s treatment to transform mobile P, W, and other HMs forms into more stable forms. The significant positive correlations between SRP, soluble W, UV254, and soluble Fe (II)/Mn, and the increased concentrations of the oxidizable HMs forms suggested the crucial role of the Fe/Mn redox in controlling the release of SRP, DOM, and HMs from sediments. The LMB + V∙s treatment resulted in SRP, W, and DOM removal rates of 74.49, 78.58, and 54.78 %, which were higher than those observed in the control group (without LMB and V∙s applications). On the other hand, the single and combined uses of LMB and V·s influenced the relative abundances of the sediment microbial communities without exhibiting effects on microbial diversity. This study demonstrated the key role of combined LMB and V∙s applications in controlling the release of P, W, DOM, and HMs in eutrophic lakes. [Display omitted] •Combined use of LMB and V∙s had a strong removal effect on internal P, W, and DOM.•LMB and V∙s additions promoted the conversion of labile P and HMs into stable forms.•The formed Fe (III) and Mn (IV) oxyhydroxides enhanced P, W, DOM, and HM adsorption.•Single and combined uses of LMB and V·s had no effects on sediment microorganisms.